Implementasi Corporate Social Responsibility PT Indonesia Power Saguling POMU dalam Program Bamboo Corner - Trianingrum, Suci; Sofiyah, Sofiyah; Kurniawan, Taufan (HK-Publishing, 2022)
AbstractThis article aims to describe the implementation of the Corporate Social Responsibility program carried out byÂ Indonesia Power Saguling POMU Ltd in the Bamboo Corner Program. This study uses a qualitative approach with data collection techniques through interviews, observations and literature studies. This research shows that Â Indonesia Power Saguling POMU Ltd has a CSR policy. This policy is the result of the embodiment of government regulations and the company's vision and mission to participate in sustainable development. The implementation of the Bamboo Corner Empowerment Program carried out by PT Indonesia Power POMU was carried out using a program innovation strategy, namely the bamboo oven. This innovation was carried out after researching the problems, potentials and prospects to increase the added value of bamboo. From this innovation, the assisted groups can save on bamboo processing operations by 53.33% and in 2022, the fostered partners can increase their income by an average of IDR 2,109,091.Keywords: Bamboo Corner, CSR, Empowerment Program Implementation, Innovation.Â AbstrakArtikel ini bertujuan untuk mendeskripsikan implementasi program Corporate Social Responsibility yang dilakukan oleh PT. Indonesia Power Saguling POMU dalam Program Bamboo Corner. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui wawancara, observasi dan studi pustaka. Penelitian ini menunjukan bahwa PT. Indonesia Power Saguling POMU mempunyai kebijakan CSR. kebijakan ini merupakan hasil dari ejawantahan peraturan pemerintah serta visi misi perusahaan untuk turut dalam pembangunan berkelanjutan. Implementasi Program Pemberdayaan Bamboo Corner yang dilakukan oleh PT Indonesia Power POMU ini dilaksanakan menggunakan strategi inovasi program yaitu oven bambu. Inovasi ini dilakukan setelah melakukan riset masalah, potensi serta prospek untuk meningkatkan nilai tambah (added value) bambu. Dari inovasi ini, kelompok binaan dapat menghemat operasional pengolahan bambu sebesar 53,33% dan di tahun 2022 ini, mitra binaan rata-rata dapat meningkatkan pendapatan sebesar Rp 2.109.091.Kata Kunci: Bamboo Corner, CSR, Implementasi Program Pemberdayaan, Inovasi.